Histopathological Study of Endometrium in Postmenopausal Bleeding (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Background & objectives: Postmenopausal bleeding is frequent in gynecology and occurs approximately in 5% to 10 % of postmenopausal women. About 10% women with postmenopausal bleeding have a primary or secondary malignancy. Common malignancies among them are endometrial or cervical carcinoma and rarely, ovarian cancer. The incidence of malignancy in postmenopausal period remains sufficiently high, so it requires immediate investigations for early diagnosis, prompt treatment and vigilant follow up. The objective of the present study is to evaluate the causes of postmenopausal bleeding based on histopathology of endometrium and the percentage of various benign, premalignant and malignant lesions in patients with post-menopausal bleeding.Methods: A retrospective study was undertaken on 78 women presenting with postmenopausal bleeding in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders (BIRDEM) Hospital, Dhaka, from July 2018 to June 2019. Histopathological reports and patient’s profile were reviewed. Causes of bleeding were identified and related to patients’ age.Results: Among of 78 cases of postmenopausal bleeding, we found 8 cases of cancer (10.26%). Among them 2 cases were cancer of uterine cervix and 6 cases were cancer of uterine corpus. Benign pathology was more frequent (63 cases: 80.77%), essentially presented with endometrial hyperplasia without atypia 20.52% cases, endometrial polyp 16.67% cases, cervical polyp 14.11% cases, leiomyoma found in 9% cases and preinvasive disease about 9% cases. Histopathological findings in 2 cases of carcinoma cervix were invasive squamous cell carcinoma and 6 cases of endometrial cancer were endometrial adenocarcinoma. Cancer increased with increasing age while the incidence of bleeding decreased with age.Conclusion: Despite the fact that benign pathology is more frequent than malignancy as a cause of postmenopausal bleeding, we must always rule out a cancer by endometrial and cervical biopsy.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 112-116